(untitled) (Fisioterapia e Pesquisa, 2023)
Critically ill subjects admitted to intensive care units (ICU) might experience physical and cognitive reserves losses that increase their vulnerability to adverse events –characterizing frailty syndrome. This study aimed to delineate the prevalence of self-reported frailty in awake and alert critically ill patients admitted to the ICU of a teaching hospital. We included adult subjects (≥18 years old), admitted for at least 48 hours in the ICU of a teaching hospital in the city of Uberaba, state of Minas Gerais (MG), Brazil, who were alertat the time of the assessment. Subjects were encouraged to report their level of frailty using the Clinical Frailty Scale (CFS). Subjects with a CFS of 1 to 3 were considered non-fragile, 4 vulnerable, and greater than 5 frail. 50 subjects aged 44 to 78 years, mostly males, were evaluated. The prevalence offrail subjects was null, one subject was considered vulnerable and the others were considered non-frail, in which category 3 prevailed in 64% of the population. When analyzing thedemographic and clinical data in the different CFS scores, no statistically significant difference was observed between gender and age in the analyzed categories. The functionalcomorbidity index was increasing in the analyzed categories, (p=0.05). The prevalence of self-reported frailty was null in critically ill patients admitted to this teaching hospital in Uberaba-MG. Self-reported frailty assessment scales may be inaccurate to identify frail subjects.